MOTIVASI DAN PENYULUHAN MERUPAKAN FAKTOR DOMINAN KEPATUHAN IBU HAMIL MENGKONSUMSI TABLET ZAT BESI - Theresia Eugenie; Syafrudin Syafrudin; Siti Masitoh (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
To overcome the problem of iron deficiency anemia in pregnant women, the government has made various efforts including the supplementation of iron tablets to pregnant women. However pravalensi anemia remains high which causes the case - cases such as abortion, childbirth preterem, barriers to growth and development of fetal and other developmental problems that are still quite high (Jumirah, 2003). Assessments of compliance of pregnant women needs to be done by health workers as one way of measuring the level of successful implementation of the supplementation of iron tablets which is a step treatment of anemia in pregnant women. The research was conducted at district health centers. Palmerah. The timing of the study during the months of November-December 2010. This research method is cross sectional. The population was pregnant women trimesters II and III which come check pregnant and taking iron tablets. Variables studied were education, knowledge, motivation, family, education of health personnel and side effects. The results showed pregnant women who are obedient to consume iron tablets is 78.7%. Results of statistical test is a significant relationship between all independent variables with dependent variabl. Motivation and family counseling from health workers is the most dominant factor related to the compliance of pregnant women taking iron tablets, with OR 4.272.